Optimal demand side management scheduling-based bidirectional regulation of energy distribution network for multi-residential demand response with self-produced renewable energy. (15th September 2022) - Nguyen, Hai-Tra; Safder, Usman; Loy-Benitez, Jorge; Yoo, ChangKyoo
Graphical abstract: Research highlights: An optimal DSM-based scheduling of energy distribution network is developed. Strategical conversation of regulated mix-generation reduced 0.92–2.28% of deficit. Self-production of installing PVs aided to increase beneficial cost consumption. The energy distribution network S.IV satisfied top 5 appliance of consumer request. Combined low-carbon energy in DSM-based distribution reduced 27.04 tons CO2 . Abstract: Global transactive energy has become more complex due to the extension of its efficiency. Thus, multi-residential demand responses pose a new challenge in the critical infrastructure of power transition networks in energy planning and management. By encompassing optimal scheduling with strategic energy decentralization, a reliable distribution network can suggest a resolution that contributes to optimize energy efficiency. This research proposed a holistic bidirectional distribution network with optimal scheduling-based demand-side management (DSM) for superior power sharing and beneficial performance. A DSM was developed to maintain equal power sharing between various mix-energy sources, providing a sub-level residential demand response program. Among several scenarios considered, the DSM-based scheduling distribution network resulted in optimum and equivalent sharing of power loads for residential demands. Moreover, the application of self-production-based renewable energy source (RES) is a novel strategy to improve imbalanced power sharing. The energy deficit and surplus can be solved by establishing a conservation strategy with self-installation-based photovoltaic panels by end-users. CO2 emissions were also estimated to elucidate the effect of the energy distribution network on the environment according to different category of energy sources. Considering satisfaction analysis based on appliance energy consumption, the energy distribution network was efficient in improving the end-user expenditure, sustaining a clean energy loading profile, and maximizing the benefit of cost.